An RNA Aptamer That Specifically Binds to the Glycosylated Hemagglutinin of Avian Influenza Virus and Suppresses Viral Infection in Cells - Hyun‐Mi Kwon; Kwang Hyun Lee; Byung Woo Han; Mi Ra Han; Dong Ho Kim; Dong‐Eun Kim (2014)
The influenza virus surface glycoprotein hemagglutinin (HA) is responsible for viral attachment to sialic acid-containing host cell receptors and it facilitates the initial stage of viral infection. In the present study, we isolated an RNA aptamer specific to the glycosylated receptor-binding domain of the HA protein (gHA1) after 12 cycles of the systematic evolution of ligands by exponential enrichment procedure (SELEX), and we then investigated if the selected aptamer suppresses viral infection in host cells. Nitrocellulose filter binding and enzyme-linked immunosorbent assay (ELISA) experiments revealed that 1 RNA aptamer, HA12-16, bound specifically to the gHA1 protein. Cell viability assay showed that the HA12-16 RNA aptamer suppressed viral infection in host cells by enhancing cell viability. Immunofluorescence microscopic analysis further demonstrated that the HA12-16 RNA aptamer suppresses viral attachment to host cells by neutralizing the receptor-binding site of influenza virus HA. These results indicate that the isolated RNA aptamer can be developed as an antiviral reagent against influenza through appropriate therapeutic formulation.